Improving Learning Outcomes Passing Chest Pass In Play Basketball With Variation Application of Learning and Modified Grade Ball SMP Santa Maria Terrain VIII Academic Year 2019/2020: Improving Learning Outcomes Passing Chest Pass In Play Basketball With Variation Application of Learning and Modified Grade Ball SMP Santa Maria Terrain VIII Academic Year 2019/2020 - Agung Nugroho; Fajar Mugo Raharjo (Journal of Midwifery and Nursing, 2020)
This study aims to determine the learning outcome passing Chest pass in playing basketball with the application of learning variations and modifications basketball in class VIII SMP Santa Maria school year 2019/2020. This research method is a method of classroom action research (PTK). From the data analysis it can be concluded that through the application of learning variations and modifications basketball, students can improve learning results on the study material passing Chest pass. Subjects in this study were students of Class VIII Terrain Maria High School Year 2019/2020, totaling 30 people. The results of the study in the first cycle shows that the learning outcomes are passing chest pass (43.33%) students who completed the study, and (56.67%) students who did not complete her studies. The results of students in techniques of passing a chest pass in the first cycle in the classical mastery learning just reached (43.33%). In the second cycle shows that the learning outcomes are passing chest pass (83.33%) students who completed the study, and (16.67%) students who did not complete their study and student learning outcomes in classical learning completeness passing chest pass on the second cycle reached (83.33%). In this study, as calculated in classical learning completeness reached 83.33% according to experts quoted by 85% of the new can be said to be completed in the classical style,